Performance and Characteristics of Mutual Funds: Evidence from the Portuguese Market - Júlio Lobão (2015)
In this paper we study the relation between fund performance and fund attributes in the Portuguese market. The sample includes 124 equity funds, bond funds and money market funds that traded in the 2004-2011 period. A comprehensive set of fund-specific characteristics, never used before in conjunction in the literature, was considered. The methodology which was adopted had two distinct phases. Firstly, we compared the returns of each category of funds with the appropriate reference markets. Secondly, the fund performance, measured by the Jensen's alpha, was used in a multi-factor model with panel data in which the independent variables were the fund attributes. The results show that Portuguese funds were, in general, not able to beat the benchmarks which is consistent with the existence of efficient financial markets. Only the fixed income mutual funds performed well. Moreover, it is possible to conclude that, for each category of mutual funds, their characteristics are useful to the investor in the moment of choosing the best funds. For example, in the case of funds that invest in Portuguese stocks, the best performance occurs among older and larger funds, funds with higher costs, funds with good past performance and funds whose trading activity is low.